2017
DOI: 10.1089/jwh.2016.6012
|View full text |Cite
|
Sign up to set email alerts
|

Women's Careers in Biomedical Sciences: Implications for the Economy, Scientific Discovery, and Women's Health

Abstract: While women have been well represented in medical school and biomedical doctoral degree programs, they do not comprise half of academic medicine faculty positions. Furthermore, there is a significant paucity of women in academic medicine leadership positions, as evidenced by the fact that only 16% of dean positions at United States Medical schools are filled by women. In this commentary, the authors review the state of women in academic medicine and argue that increased representation of women in the academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…For example, women earned 49% of PhDs in biological sciences in 2005 and 52% in 2010 ( 4 ), yet composed 44% of assistant professors with biology PhDs in 2015 ( 5 ). Similar discrepancies between PhD holders and faculty representation persist in academic medicine ( 6 ). In addition, interest in faculty positions varies by gender across successive career stages; women pursuing biomedical science PhDs, as well as female postdocs at the National Institutes of Health (NIH), report less interest than men in becoming principal investigators ( 7 , 8 ).…”
mentioning
confidence: 92%
“…For example, women earned 49% of PhDs in biological sciences in 2005 and 52% in 2010 ( 4 ), yet composed 44% of assistant professors with biology PhDs in 2015 ( 5 ). Similar discrepancies between PhD holders and faculty representation persist in academic medicine ( 6 ). In addition, interest in faculty positions varies by gender across successive career stages; women pursuing biomedical science PhDs, as well as female postdocs at the National Institutes of Health (NIH), report less interest than men in becoming principal investigators ( 7 , 8 ).…”
mentioning
confidence: 92%
“…The later finding might especially reflect the lack of senior females in this field, as last authors tend to be senior. This conclusion is supported by Plank-Bazinet’s, et al [ 4 ] study which found a significant scarcity of women in academic biomedical leadership and senior positions. Having controlled for several factors, it was found that female first and last-authored papers had a small but significant citation advantage of 4.7% and 5.5% compared to male-authored papers.…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…Furthermore, the proportion of women amongst researchers in health and life sciences between 2011–2015 was shown to be overall higher than men researchers, as per the Gender in the Global Research Landscape Report [ 2 ]. Despite the gender parity in degree recipients and the number of researchers, women remain underrepresented among tenure-track biomedical faculty at research institutions [ 3 ] and are underrepresented in the faculties of medicine and life sciences, as well in senior positions [ 4 ]. In 2016 in the EU, women represented totally 27% of grade A academic staff in health and medical sciences [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional steps, such as restoring the NIH budget to its inflation-adjusted 2003 levels or even higher (to account for population expansion), would be required to ensure that biomedical research in the US remains competitive on the international stage. Meanwhile, concerned scientists are discussing ideas and principles, and agency officials are exploring additional mechanisms, to support a robust research ecosystem in the face of finite resources (see, for example, Levitt and Levitt, 2017 ; Alberts et al, 2014 ; Lorsch, 2015 ; FASEB, 2015 ; Pickett et al, 2015 ; Blume-Kohout and Adhikari, 2016 ; Schaller et al, 2017 ; Heggeness et al, 2017 ; Plank-Bazinet et al, 2017 ). A good example is the Maximizing Investigators’ Research Award (MIRA) program, a NIGMS program to “fund people, not projects” ( NIGMS, 2017 ).…”
Section: Harnessing Additional Talent and Its Limitationsmentioning
confidence: 99%